Desenvolvimento da periodontite apical em ratos sadios e com diabetes tipo 2: efeito do tratamento com metformina - Machado, Camilla dos Santos Tibúrcio (2014)
Diabetes is classified as a metabolic disorder, since its establishment promotes several systemic and oral changes. One of the causes of these alterations is the excess of reactive oxygen species (ROS) presents in the diabetic patient tissues, leading to oxidative stress increase. Metformin, the anti-hyperglycemic more used in the type-2 diabetics treatment, is a ROS scavenger. Furthermore, recent studies have shown a bone repair increase attributed to the drug. However, there are not reports searching the relationship between metformin and apical bone repair in the type-2 diabetes individuals. Therefore, the aim of this study was evaluate the treatment effect with metformin on the development of apical periodontitis (AP) in healthy and type-2 diabetes rats. Addicionally, biochemical parameters related to metabolic disorder were evaluated in order to complement the pharmacological study. For this purpose, forty eight Wistar rats were fed either with a standard diet (SD) or high fat, low protein, moderate carbohydrate diet (HFLPMC). Rats in each diet were divided into three subgroups: i) saline (daily/four wk); ii) metformin (500mg/kg, daily/two wk); iii) metformin (500mg/kg, daily/four wk). At the sixth experimental week, the pulp chambers of first mandibular molars were exposed in order to permit the AP development. Glucose tolerance test was performed in the week before euthanasia. At the tenth experimental week, the animals were euthanized and it was collected the fallowing structures: liver, abdominal adipose tissue, interscapular brown adipose tissue and mandible. Also, it was collected blood to determine levels of plasma insulin, total and HDL cholesterol. Catalase and reduced glutathione (GSH) were measured and the size of apical periodontitis was estimated from radiographs of the mandible. After 30 minutes of sucrose administration, the rats fed with HFLPMC diet presented greater blood glucose levels than the ones fed with SD. However, the metformin administration did not affect this concentration. Moreover, plasma insulin levels were higher in the HFLPMC+Saline group than in the SD+Saline group. Catalase levels in the HFLPMC+Saline group were significantly lower than SD+Saline group (p = 0,0267) and metformin increased these levels in the animals fed with HFLPMC diet. It was observed a similar behavior with GSH levels. In the radiographic analysis, treatment with metformin did not affect the AP size. Therefore, based on the results, we suggest that metformin has not a positive effect over the bone metabolism.